1852 Ala. Code 588 - (:unkn) unknown (My University, 1852)
§ 3274: Prohibited the concealed carry of a pistol, or any other firearms, while not being threatened or having good reason to believe attack is imminent. §3273 also prohibited the concealed carry of Bowie-knives, other similar knives, and air guns. Violators fined not less than fifty, but no more than three hundred dollars.
Keywords: CARRY - CONCEALED